Multimers of the fibroblast growth factor (FGF)-FGF receptor-saccharide complex are formed on long oligomers of heparin. - Harmer, N; Robinson, C; Adam, L; Ilag, L; Robinson, C; Gallagher, J; Blundell, T (2006)
The minimal signalling unit for tyrosine kinase receptors is two protomers dimerized by one or more ligands. However, it is clear that maximal signalling requires the formation of larger complexes of many receptors at discrete foci on the cell surface. The biological interactions that lead to this are likely to be diverse and have system specific components. In the present study, we demonstrate that, in the FGF (fibroblast growth factor)-FGFR (FGF receptor) system, multimers of the minimal complex composed of two FGF1 and two FGFR2 protomers can form on a single chain of the co-receptor heparin. Using size-exclusion chromatography, we show that two complexes can form on heparin chains as small as 16 saccharide units. We also show by MS that discrete complexes containing exactly two copies of the minimal signalling unit are formed. However, the doublet of complexes appears to be less co-operative than the formation of the 2:2:1 FGF1:FGFR2:heparin complex, suggesting that this mechanism is one of a number of weaker interactions that might be involved in the formation of a focal complex on the cell surface.